THE INFLUENCE OF ORGANIZATIONAL CULTURE, KNOWLEDGE AND SOCIAL CAPITAL MANAGEMENT STRATEGIES ON SMALL AND MEDIUM BUSINESS PERFORMANCE IN THE FOOD INDUSTRY - Siti Maemunah (Business and Entrepreneurial Review, 2019)
The research topic is to examine the influence of organizational culture, knowledge management strategies and social capital on business performance in small and medium-sized businesses in the food industry. The research method is quantitative by using the SEM methodology and primary data taken using a questionnaire. The population in this study is food industry SMEs in DKI Jakarta by 200. The research respondents were directors, managers and decision makers. The results of hypothesis testing indicate that organizational culture and knowledge management strategies on business performance in small and medium businesses have a positive and significant impact. While the results of testing the social capital hypothesis on business performance are positive but not significant. The next research is recommended to take respondents at the company or corporation level. The next research is suggested to add qualitative research so that it deepens the conclusions obtained.